PENINGKATAN KAPASITAS UMKM AGRIBISNIS MELALUI PELATIHAN DIGITALISASI USAHA DAN PENDAMPINGAN LEGALITAS HUKUM BERBASIS SISTEM INFORMASI - Putranto, Afif Hendri Putranto; Hasirun, Hasirun; Sumaya, Pupu Sriwulan Sumaya (Awatara Publisher, 2025)
This community service program aims to enhance the capacity of agribusiness MSMEs in Java through business digitalization training and legal assistance using an information system. The main problems faced by MSMEs include low digital literacy, the absence of structured transaction records, and limited understanding of legal business requirements. This activity was conducted using a participatory and transdisciplinary approach involving agribusiness, legal, and informatics disciplines. The results show that participants successfully implemented digital bookkeeping, utilized social media for marketing, and understood as well as managed legal documents such as business permits and halal certification. Moreover, the web-based information system developed is independently usable by MSMEs for business management and legal reminders. This program also fostered inter-MSME networking and encouraged participant-driven sustainability initiatives. The social and economic impacts confirm that integrating digital and legal approaches is highly relevant to addressing the real needs of MSMEs. This program may serve as a replicable model for other regions with similar characteristics.